Roquin – a multifunctional regulator of immune homeostasis - Schaefer, J. S. (Genes Immun, 2015)
Roquin-1 (Rc3h1) is an E3 ubiquitin ligase originally discovered in a mutational screen for genetic factors contributory to systemic lupus erythematosus-like symptoms in mice. A single base pair mutation in the Rc3h1 gene resulted in the manifestation of autoantibody production and sustained immunological inflammation characterized by excessive T follicular helper cell activation and formation of germinal centers. Subsequent studies have uncovered a multifactorial process by which Roquin-1 contributes to the maintenance of immune homeostasis. Through its interactions with partner proteins, Roquin-1 targets mRNAs for decay with inducible costimulator being a primary target. In this review, we discuss newly discovered functions of Roquin-1 in the immune system and inflammation, and in disease manifestation, and discuss avenues of further research. A model is presented for the role of Roquin in health and disease.